Small-sided games for young athletes: is game specificity influential? - Harrison, C. B.; Kilding, A. E.; Gill, N. D.; Kinugasa, T. (Journal of Sports Sciences, 2014)
This study aimed to quantify and compare the physiological, physical and technical demands of a sport-specific and non-sport-specific small-sided game (SSG) in young athletes. Ten male soccer players (mean ± SD: age, 13.0 ± 0.3 years, O2peak, 54.4 ± 4.9 ml/kg·min) completed 3 vs. 3 and 6 vs. 6 soccer and "bucketball" SSGs twice. Games lasted for 16 min and were performed in a randomised order, at least 48 h apart. Movement patterns and heart rate were measured using 4 Hz global positioning systems. Technical skill executions were assessed by video analysis and ratings of perceived exertion (RPE) using the Borg scale (RPEs, 6-20). Total distance (4.9 ± 4.1% and 8.3 ± 6.6%), distance at 7-12.9 km/h (14.5 ± 12.5% and 14.9 ± 16.1%), total possessions (14.7 ± 18.0% and 12.9 ± 18.9%) and percentage of successful passes (24.1 ± 11.7% and 30.1 ± 17.6%) were higher for bucketball compared to soccer (3 vs. 3 and 6 vs. 6, respectively). Total distance at 13-17.9 km/h was higher for 6 vs. 6 than 3 vs. 3 bucketball (32.3 ± 21.2%). There was likely substantial difference for %HRpeak (89.5 ± 3.1 vs. 87.4 ± 2.8 b/min) and time above 90% HRpeak (570 ± 288 s vs. 361 ± 288 s) between bucketball and soccer (3 vs. 3 and 6 vs. 6, respectively). Young players travelled further at higher overall speeds, experienced higher physiological workloads and performed more successful technical executions during the non-sport-specific SSG.